CGRP monoclonal antibody for preventive treatment of chronic migraine: An update of meta‐analysis. Issue 2 (18th January 2019) - Han, Lin; Liu, Yao; Xiong, Hai; Hong, Peiwei
Abstract: Background: CGRP monoclonal antibody (mAb) is a promising preventive treatment for episodic migraine and has been approved by US FDA recently. But the treatments for chronic migraine are rare. Therefore, we performed meta‐analysis to assess the efficacy and safety of CGRP mAbs in preventing chronic migraine. Methods: Database including Cochrane Library and PubMed were systematically searched for randomized controlled trials (RCTs) which are about CGRP mAb in preventing treatment of chronic migraine. Evaluating the bias and quality of RCTs was carried out according to the Cochrane collaboration's tool for assessing risk of bias. The data analysis was carried out by reviewer manager 5.2. Results: Totally, 6 articles enrolled in the present meta‐analysis, including 4 independent clinical trials and 3, 166 patients. After pooled analysis, it indicated that CGRP mAb improved 50% responder rate (OR = 2.42, 95% CI = [2.04, 2.87], I 2  = 0%, p  < 0.00001) and 75% responder rate (OR = 1.95, 95% CI = [1.30, 2.91], I 2  = 0%, p  = 0.001), as compared with placebo. And there was no difference in incidence of adverse events between CGRP mAb group and placebo group except incidence of injection site discomfort. Conclusions: CGRP mAb is an effective and safety preventive treatment for chronic migraine. Abstract : Calcitonin gene‐related peptide monoclonal antibody (CGRP mAb) is a promising preventive treatment for migraine. And erenumab is approved by U.S. Food and Drug Administration in preventing episodic migraine recently. And the present meta‐analysis shown that CGRP mAb is an effective and safety treatment for chronic migraine, of which preventive treatments are rarely.